Intermediate activities while commuting - José Ignacio Giménez-Nadal; José Alberto Molina; Jorge Velilla (Global Labor Organization (GLO), 2022)
Recent analyses have shown that commutes to and from work are not symmetric, suggesting that intermediate activities are at the root of these asymmetries. However, how intermediate activities interact with trips to and from work is an unexplored issue. Using data from the American Time Use Survey 2003-2019, we analyze what activities workers do while commuting, and compare measures of commuting when intermediate activities are included or excluded as part of the commuting trip. We show that commuting is underestimated if measured with the Time Use Survey lexicon. Such differences are especially significant in commuting from work. Furthermore, gender comparisons of commuting are affected by the inclusion of intermediate while commuting, with gender differences narrowing when intermediate activities are considered. Our results contribute to the analysis of commuting behavior, by proposing new identification strategies based on intermediate non-trip episodes, and by showing how commuting interacts with other non-commuting activities.
Keywords: J22; R41; 330; Commuting time; Trip behavior; Intermediate activity; Time use data; American Time Use Survey